2016
DOI: 10.1177/0268355516635466
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of O-(beta-hydroxyethyl)-rutosides in reducing the incidence of superficial venous insufficiency in patients with calf muscle pump dysfunction

Abstract: Objective We aimed to evaluate the efficiency of O-(beta-Hydroxyethyl)-rutosides (Oxerutin) in reducing the incidence of venous system disease among patients with calf muscle pump dysfunction secondary to immobilization due to lower-limb fractures. Methods A total of 60 patients with lower-limb fractures and immobilized in plaster casts were included in this study randomized into control (n = 30; mean: 30.37 ± 6.03 years; 73.3% males; no treatment) and experiment (n = 30; mean: 31.67 ± 4.76 years; 66.6% males;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Flavonols’ effects on the incidence of venous-system disease, advanced glycation end products (AGEs), and biomarkers of heart health risk have also been reported in recent clinical studies [ 89 , 93 , 94 , 95 ]. Blood biomarkers of heart health, such as homocysteine (Hcy), high-sensitivity C-reactive protein (hs-CRP), oxidized LDL (ox-LDL), gamma-glutamyl transferase (GGT), uric acid, and blood lipid profile were investigated among the Russian population under a multivitamin, multimineral, and phytonutrient (VMP) supplement which contained quercetin.…”
Section: Clinical Studies On Flavanol Interventions—an Update From Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonols’ effects on the incidence of venous-system disease, advanced glycation end products (AGEs), and biomarkers of heart health risk have also been reported in recent clinical studies [ 89 , 93 , 94 , 95 ]. Blood biomarkers of heart health, such as homocysteine (Hcy), high-sensitivity C-reactive protein (hs-CRP), oxidized LDL (ox-LDL), gamma-glutamyl transferase (GGT), uric acid, and blood lipid profile were investigated among the Russian population under a multivitamin, multimineral, and phytonutrient (VMP) supplement which contained quercetin.…”
Section: Clinical Studies On Flavanol Interventions—an Update From Th...mentioning
confidence: 99%
“…O-(b-Hydroxyethyl)-rutosides (Oxerutin) are a standardized combination of the semisynthetic flavonoids created by replacing the hydroxyl groups with hydroxyethyl groups in the naturally occurring flavonol rutin. Yildiz et al showed that 6–8-week Oxerutin intake reduced the incidence of superficial venous reflux in the distal crural veins in cast immobilization for lower-limb-fracture patients [ 95 ].…”
Section: Clinical Studies On Flavanol Interventions—an Update From Th...mentioning
confidence: 99%